Analysis of mechanical behavior of fiber-glass plastic with hole pattern using digital image correlation and acoustic emission methods - E. M. Strungar; D. S. Lobanov; E. A. Chebotareva; Y. V. Kochneva (Fracture and Structural Integrity, 2024)
In this paper, tensile tests of specimens with a pattern of holes made of fiber-glass plastic based on combined epoxy and phenol-formaldehyde resins are carried out in order to study the processes of damage accumulation and tension fracture. The Vic-3D video system is used to evaluate damage development and inhomogeneity of strain localization during loading. Continuous recording of acoustic emission signals is carried out during the tests, resulting in obtaining data on fracture mechanisms in the material. Ranges of peak frequencies are identified. Surface analysis of specimens was carried out using a microscope. A significant reduction in strength occurs due to the presence of a circular hole in the material, although additional holes do not exacerbate this effect. Fracture patterns of specimens with a hole pattern have been analyzed, and different "paths" of fracture have been observed. The comparison of strain fields obtained on the basis of application of three-dimensional digital optical system with the configuration of strain fields constructed as a result of numerical modeling by the finite element method has been carried out. It is found that the strain fields for different open hole patterns are quantitatively and qualitatively similar and identical